MENINGKATKAN KOMPETENSI GURU SAAT PANDEMI COVID-19 DENGAN E-LEARNING MENGGUNAKAN DIRECT INSTRUCTION - Udik Pudjianto; Nia Saurina; Lestari Retnawati (Aptekmas Jurnal Pengabdian pada Masyarakat, 2022)
Universitas Wijaya Kusuma Surabaya (UWKS) in collaboration with BPPAUD & DIKMAS East Java has improved teacher competence, through understanding how to operate e-learning for secondary education units in East Java, namely SMKN 13 Surabaya. This Community Service activity applies the Direct Instruction learning model for teachers during the COVID-19 pandemic. The target of this activity is the teacher of SMKN 13 Surabaya in the Computer Network Engineering department, with 10 subjects as the subject. The results of this activity have been achieved that there has been an increase in teacher competence in using e-learning operations after following the Direct Instruction learning model, which is 41.46 points. This value of 41.46 has met the minimum completeness criteria mastery of e-learning materials that have been achieved by teachers of SMKN 13 Surabaya.